A graphite enclosure assisted synthesis of high-quality patterned graphene on 6H–SiC by ion implantation. (February 2021) - Chen, Yuhan; Zhao, Yunbiao; Han, Dong; Fu, Dongpo; Chen, Yi; Zhou, Danqing; Li, Yue; Wang, Xu; Zhao, Ziqiang
Abstract: Synthesis of high-quality graphene on insulating/semiconducting substrate is important in the development of future graphene-based electronic device technology. In this paper, an approach of ion implantation followed by annealing in a graphite enclosure was used to directly produce high-quality patterned graphene on 6H–SiC. Specifically, 5 keV argon ions were implanted in single-crystal 6H–SiC followed by thermal annealing in a graphite enclosure to synthesize graphene using the graphite enclosure as a carbon source. After annealing, carbon atoms, coming from graphite enclosure and SiC itself, migrate to the substrate surface and self-assemble into graphene. In contrast with present graphene production techniques, our approach requires a significantly lower temperature of ∼1100 °C and avoids the use of a large amount of gases, hydrogen etching and transfer process. Moreover, in this approach, patterned graphene can be synthesized by precisely controlling the growth site. To understand the growth mechanism, a brief model based on the influence of ion implantation, heat preservation time and graphite enclosure was established. Our work has established a convenient and economical approach of graphene production and expects to spark more interest in graphene-based electronic devices. Graphical abstract: Image 1